Penguatan Nilai-nilai Ahlussunnah wal Jama’ah dalam Pembelajaran bagi Guru Madrasah Ibtidayah Kota Semarang: Pengabdian - Farda, Ummu Jauharin; Shobirin, Ma’as; Rinjani, Ersila Devy; Martanti, Fitria; Putri, Linda Indiyarti; Ghoni, Aris Abdul; Herningtyasari, Gadis; Nada, Ana Quthratun; Ulumuddin, Imam Khoirul; Husna, Muhammad Ahsanul; Nisa’, Asmi Adibah Khoirun; Adawiyah, Robiatul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The community service program to strengthen the understanding and internalization of Ahlussunnah wal Jama'ah (Aswaja) values ​​for Elementary Madrasah (MI) teachers in Semarang City was implemented through an Asset Based Community Development (ABCD) approach. This activity aims to increase the capacity of teachers in understanding and integrating Aswaja values ​​in learning and madrasah culture. The program implementation began with a needs analysis through interviews with teachers, madrasah principals, and the coordinator of the Elementary Madrasah Teacher Working Group (KKGMI). The activity stages included training, workshops on developing teaching materials, mentoring, and the preparation of Aswaja-based teaching modules. The evaluation results showed a significant increase in teachers' understanding of Aswaja values ​​(tawasuth, tawazun, tasamuh, and i'tidal) as demonstrated through pretest and posttest results. Teachers were also able to design teaching modules that include the values ​​of tawasuth, tawazun, tasamuh, and i'tidal contextually. Furthermore, ongoing discussion initiatives have been established in several madrasas as a commitment to internalizing Aswaja values. However, implementation still faces challenges, such as time constraints.